Shape and diameter control of C60 fullerene micro-stains by evaporation of aqueous SDS-fullerene dispersion drops - Doganci, Merve D.; Erbil, H. Yildirim (Elsevier Science Bv, 2013)
The effect of the surface free energy of substrates such as glass slide, polymethyl methacrylate, polystyrene, polypropylene and Teflon-FEP was investigated on the shape and diameter of fullerene (C-60) stains which were obtained by evaporation of aqueous sodium dodecyl sulfate/fullerene dispersion drops having different SDS/C-60 fullerene compositions and different drop volumes. It was found that the surface free energy of the substrates was the most important parameter to control the shape and the diameters of the formed SDS/C-60 fullerene deposits and a good linear relationship was obtained between the stain diameter and surface free energy of the substrates. Uniform circular fullerene/SDS deposits were obtained on polystyrene surfaces. (C) 2013 Elsevier B.V. All rights reserved.
1st International Workshop on Wetting and Evaporation of Droplets of Pure and Complex Fluids -- JUN 17-20, 2013 -- Marseilles, FRANCE
Keywords: Drop evaporation; Fullerene; C-60; Sodium dodecyl sulfate; Stain; Deposit